Real money : money and payment systems from an Islamic perspective - Mydin Meera, Ahamed Kameel (IIUM Press, 2009)
The present unstable and anarchic global monetary system is primarily due to multiple national currencies that are not anchored to anything rela like gold. An urgent revamp of the global monetary system is, therefore, necessary to 'save' the world from falling into the brink of destruction and misery. This edited book discusses this much needed alternative monetary system that is based on real money as opposed to fiat money. A real money is a commodity-based money. Historically, gold and silver were the dominant commodity monies that provided the world with a stable and just international unit of account and means of payments. Under gold standard, central banks were not needed and the world shared a common currency without political integration. The book, nevertheless, approaches this monetary issue from an Islamic viewpoint. Gold and silver were indeed the monetary standards in the Shari'ah. The rulings on mu'amalat, zakat, hudud and mahr were all based on gold and silver. An important aspect of this book is that it discusses how real-money payment systems could be operated practically given present circumstances, laws and infrustructure.